2000
DOI: 10.1002/1096-9861(20010115)429:3<419::aid-cne5>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical differentiation of functionally distinct populations of autonomic neurons

Abstract: The coeliac ganglion of guinea pigs displays a unique topographical arrangement of neurochemically and functionally distinct populations of sympathetic neurons. The authors used multiple-labeling immunohistochemistry to investigate the neurochemical differentiation of these neurons during embryonic and fetal development. Sympathoadrenal precursors, located on either side of the abdominal aorta, were intensely immunoreactive for tyrosine hydroxylase (TH-IR), neurofilament, and the human natural killer 1 antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…However, our studies suggest that it will be essential to determine whether the SOM‐LIR in sensory neurons is due to somatostatin or cortistatin. Our data also raise the issue of whether the subpopulation of prevertebral sympathetic neurons observed in the celiac ganglion of adult guinea pigs that label with antibodies prepared against SOM‐14 are actually expressing somatostatin or cortistatin (Anderson et al,2001).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, our studies suggest that it will be essential to determine whether the SOM‐LIR in sensory neurons is due to somatostatin or cortistatin. Our data also raise the issue of whether the subpopulation of prevertebral sympathetic neurons observed in the celiac ganglion of adult guinea pigs that label with antibodies prepared against SOM‐14 are actually expressing somatostatin or cortistatin (Anderson et al,2001).…”
Section: Discussionmentioning
confidence: 81%
“…Neurons with somatostatin‐like immunoreactivity (SOM‐LIR) are also found in enteric, sympathetic, and parasympathetic ganglia of the mature autonomic nervous system. SOM‐LIR is expressed in cholinergic enteric neurons and a subset of neurons in parasympathetic ganglia; in the superior cervical ganglion, SOM‐LIR is expressed in a small subpopulation of neurons (Lundberg et al,1982; Wright and Luebke,1989), whereas more SOM‐LIR neurons are seen in trunk prevertebral ganglia (Hökfelt et al,1977; Anderson et al,2001). It has been assumed that SOM‐LIR is due to the presence of SOM‐14 or its N‐terminal extended SOM‐28; however, with the discovery of two genes that encode highly similar mature peptides, it is not clear whether the SOM‐LIR observed is actually due to transcription of the PSS1 or PSS2 gene.…”
mentioning
confidence: 99%
“…The presence of two maxima, one at very low NPY concentrations (pM) and one at very high concentrations (10 nM) not only indicates that NPY is one of the most potent angiogenic peptides known, but also that it can induce blood vessel formation over a wide range of concentrations. For instance, NPY-induced angiogenesis can occur in tissues that contain low NPY concentrations, such as the nonsympathetically innervated aorta or growing organs lacking a mature NPY system (29). Nevertheless, it can occur in tissues containing high NPY concentrations, such as the heart, mature vessels, or muscles during high sympathetic activity induced by stress, ischemia, or injury (11,18,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…NPY-driven angiogenesis has been proposed to be bimodal at least in vitro (at low and high concentration, 10 -12 and 10 -8 M, respectively) and through oligomerization of Y1-, Y2-, and Y5-R. These data might explain the in vivo NPY-induced angiogenesis both in tissues that contain low NPY concentrations, such as the nonsympathetically innerved aorta or growing organs lacking a mature NPY system [46] and in tissues containing high NPY concentrations, such as the heart, mature vessels or muscles during high sympathetic activity induced by stress, ischemia, or injury [34,47]. Moreover, treatment with NPY and specific compounds, such as NPY 3-36 (Y2-R/Y3-R/Y5-R agonist), [Ala 31 , Aib 32 ]-NPY (Aib stands for -amino isobutyric acid; specific Y5-R agonist), [Ahx [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] ]-NPY (specific Y2-R agonist) and specific Y2-R antagonist (BIIE0246TF) and Y5-R antagonist (CGP71683A) (see chemical structures in [111]), have demonstrated that: a) heterotrimers (Y1-R/Y2-R/Y5-R) are required for migration, b) heterodimers (Y1-R+Y2-R; Y1-R+Y5-R, or Y2-R+Y5-R) for proliferation and c) monomers (Y1-, Y2-, or Y5-R) for differentiation [11].…”
Section: Npy In Angiogenesismentioning
confidence: 99%